Reconstruction of Indigenous Forests Planning Policy in Way Kanan Regency Following the Ruling of the Constitutional Court on Traditional Forest - Erina Pane (Universitas Lampung, 2017)
Constitutional Court Decision No.35/ PUU-X/2012 restored the function of indigenous forests to be managed by the indigenous peoples. The ruling establishes that indigenous forest is no longer a part of the state forest but part of the forest rights. Forest rights no longer only include forests on lands of the natural/legal entity but also are located in the area of indigenous peoples. The problem in this research is how the reconstruction of indigenous forest planning policy in Way Kanan regency after the issuance of the Constitutional Court Decision No. 35 / PUU-X / 2012 on Traditional Forest. The research used here is normative juridical-empirical. The data used is secondary data and primary data, and then is performed by juridical qualitative data analysis. Based on the research results, the arrangement of indigenous forests done by Way Kanan District Government is started with the assistance and mediator, data collection, research conduct and the confirmation of the existence of customary law communities along with indigenous areas, cooperating with the partnership between indigenous peoples and the concessionaires of Forest Management Rights (HPH), and accelerate the formation Regional Regulation on the Recognition of Indigenous Peoples. Indigenous forest planning policy was blocked because Way Kanan Regional Regulation that specifically related to customary law communities has not been established, there is something confusing associated with the administration of indigenous forests and the intervention of interests of the party holding Forest Management Rights (HPH). Keyword: Reconstruction, Regulation, Indigenous Forest